Institutional Structures of Latin American Countries for Accession and Participation in the OECD - Lucas da Silva Tasquetto; Magali Favaretto Prieto Fernandes; Milena da Fonseca Azevedo (Contexto Internacional)
Abstract This article delineates the institutional structures established by Mexico, Chile, Colombia, and Costa Rica to facilitate their accession to the Organization for Economic Cooperation and Development (OECD). The analysis delves into the political and economic contexts surrounding each country’s accession process, identifying key institutions and stakeholders domestic reforms required, and particular initiatives from each country, including institutional innovations and adapted procedures. Notably, each country exhibits unique institutional frameworks and adjustments, with varying prominence given to individuals and governmental entities based on constitutional, legal, and political-administrative configurations. We argue that, despite the uniqueness of each process, from an institutional standpoint, decisions concerning accession and the management of the process predominantly revolve around the Presidency and entities corresponding to the Ministry of Finance and the Ministry of Foreign Affairs, with variations in the preponderance of these bodies, and their leadership and coordination roles. Framing entry into the OECD primarily as a technical matter tends to justify the central role of the Ministries of Finance and affiliated bodies within the Presidency, aligned with the OECD’s liberal approach. Moreover, accession to the OECD often complements and/or legitimizes processes of trade openness and structural reforms, spurring consolidation of factions within domestic institutions.